Сучасні міфології масової свідомості в повсякденному бутті українського суспільства - Борейко, Ю. Г.; Boreyko, Y. G. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано вплив неоміфологій на масову свідомість сучасного українського суспільства. З’ясовано, що в масову свідомість за допомогою технологій свідомого конструювання міфологій впроваджуються спрощені форми стійких уявлень про факти повсякденності, які ґрунтуються на культурних архетипах. Associate Professor of Philosophy and Religious Studies Department of the Social Studies Institute at Lesya Ukrainka Eastern European National University. As the technology is «secondary» myth-making in the public consciousness introduced artificially constructed stereotypes based on binary oppositions that have formed in the depths of the folk tradition. This allows you to share in the mass consciousness of the simplified forms of stable representations of the facts of reality and use technology conscious shaping of myths based on cultural archetypes. Sacralization through national symbols used to add weight mythologizing of events and personalities. PR-technology, connecting to the already recorded in the mass consciousness of the information, change it by working with the myths. Mass consciousness is related to the collective unconscious, under the influence of the media becomes a breeding ground for myth-making. Slavic animistic images are supplemented by later – the guardian angels of the new and enhanced mythological entities like poltergeist, aliens, bigfoot – extremely stable not only in the daily performances, but also in popular culture. The latter is increasingly drawn to the autochthonous mythological images and symbols, replacing them with modern stereotypes and brands: sports team «Borisfen», beer «Sarmatian» and «Slavutich», kvass «Jarilo», cosmetic grade «Lada», salting «Veres» and others. Mythological characters are changed in modern everyday reality does not convey the mortgaged in their original meaning and connotation of the traditional symbols of thought.
New Mythology Mass Consciousness in Everyday Being Ukrainian Society
Keywords: нові міфології; new mythology; «вторинна» міфотворчість; «secondary» myth-making; масова свідомість; mass consciousness; повсякденність; everyday; постмодерн; postmodern; українське суспільство; Ukrainian society